2023
DOI: 10.5152/eurasianjmed.2022.22321
|View full text |Cite
|
Sign up to set email alerts
|

The Shining Star of the Last Decade in Regional Anesthesia Part-I: Interfascial Plane Blocks for Breast, Thoracic, and Orthopedic Surgery

Abstract: Regional anesthesia has benefits beyond just treating acute postoperative pain. Interfascial plane blocks, which have been very popular with ultrasound in recent years, function primarily by administering a high volume of a local anesthetic to the fascial plane. Contrary to traditional peripheral nerve blocks, the targeted nerve or structure in interfacial plane blocks is not fully defined, and the indications have not been fully revealed yet. Anatomical, cadaveric, and radiological studies show how effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Additionally, they demonstrated that sensory blockage was successfully achieved in the T6–T10 dermatomes along the anterior axillary line and T6–T9 dermatomes along the midline [ 12 ]. We administered a substantial amount of local anesthetic since we believed that more analgesia may be attained by utilizing a larger volume for fascial plane blocks, drawing from prior research findings and our previous experiences [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they demonstrated that sensory blockage was successfully achieved in the T6–T10 dermatomes along the anterior axillary line and T6–T9 dermatomes along the midline [ 12 ]. We administered a substantial amount of local anesthetic since we believed that more analgesia may be attained by utilizing a larger volume for fascial plane blocks, drawing from prior research findings and our previous experiences [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, regional anesthesia techniques are performed for postoperative analgesia management after cardiac surgery. 1,2 The sternum is innervated by the anterior branches of the T2–T6 intercostal nerves (Figure 3A). In cardiac surgery with median sternotomies, drainage tubes are commonly placed in the epigastric region.…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors contribute to pain after cardiac surgery including median sternotomy, thoracic retraction, sternal wires, and chest tubes. 1–4 Parasternal fascial plane blocks have become popular and target the anterior branches of the T2–T6 intercostal nerves. Although these blocks can effectively relieve pain associated with sternotomy, they do not mitigate pain from chest tubes that may be placed in the epigastric region through the rectus abdominis muscle (RAM).…”
mentioning
confidence: 99%
“…Interfascial plane blocks are performed daily in anesthesia practice, and novel blocks have been defined. 3 A pericapsular nerve group (PENG) block is an interfascial plane block that targets articular branches of the femoral and accessory obturator nerves. 4 Ahiskalioglu et al 5 reported that a high-volume PENG block can act as a lumbar plexus block and can be used as the main anesthetic during resections of thigh lesions.…”
mentioning
confidence: 99%